Faktor-Faktor Yang Memengaruhi Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Vidyarto Nugroho, Valensiska, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this research is to determine and examine related to the effect of financial performance, capital structure, and liquidity on firm value and examine the effect of moderation from firm size. This research makes manufacturing companies listed on the Indonesia Stock Exchange during the period of 2018-2020 as the population in this research. The sample used in this research is as many as 81 companies that have been selected through purposive sampling method. To perform data processing and analysis, this study uses panel data regression with Microsoft Excel 2010 and E-Views 12. The results obtained in this research are financial performance has a positive effect on firm value, capital structure has a positive effect on firm value, and liquidity has no effect on firm value, while the results using moderation show that firm size cannot moderate the effect of financial performance, capital structure and liquidity on firm value.